Teaching power electronics using the switching function approach - Darwish, Mohamed K.; Marouchos, Christos (My University, 2012)
The teaching of Power Electronics at university Level can be simplified and can be more effective by employing the Switching Function Technique. A unified approach to the operation and analysis of any power converter circuit is possible. The authors tried this approach for a number of years at the Cyprus University of Technology and at Brunel University. This teaching approach is based on the identification of the appropriate switching function which can be applied to a power converter. The switching function is a series of pulses of unity magnitude and it is expressed as a series of sinusoids and its parameters are the ON period of the pulses as well as their phase angles. Analytical expressions of current and voltage waveforms are derived at any point of the circuit -preferably the input and output- as a series of sinusoids. This makes the identification of the order of the harmonics straightforward and the calculation of harmonic magnitude & phase, THD, PF etc. possible.
Keywords: Power electronics; Electric switchgear; Switching circuits; Harmonic analysis